AB0797 Long term prospective multicenter randomized placebo-controlled study of hyaluronic acid in small joints osteoarthritis (SJOA). (15th June 2017) - Tsvetkova, E; Denisov, L; Panasyuk, E; Nasonov, E
Abstract : Objectives: Assessment of the efficacy, tolerability and period of aftereffect of the single administration into 1st carpometacarpal and 1st metatarsophalangeal OA joints of 1.0 ml (20mg) of hyaluronic acid (Durolane) as compared with placebo. Methods: The study included 120 pts with OA of small hand joints or feet, pain intensity >40 mm by VAS and consisted of two phases: "blind" phase up to 24 weeks, period of assessment of long term efficacy results – 48 weeks. The efficacy was assessed by 40% pain subsiding, index AUSCAN (for the hand), dose of NSAID, total effect assessment. Results: Both groups were comparable by basic clinical criteria, 40% pain subsiding by VAS (mm) was noted in experimental group to 24th week in 79.7%, in the placebo group – 30% (chi-square: p<10 -5 ), relation of chances (OR) equal to 9.1 (3.9–21.1). Dispersion analysis of pain, stiffness and function of AUSCAN index revealed reliable differences between Durolane and placebo. Statistically significant difference (p<0.0001) according to assessment of general condition by the doctor and patient were found out in experimental group from the 4th week and were stable till 48th week. Adverse effects related to the therapy were not found. NSAID dose was decreased in 45.7% in experimental group and in 30% in placebo group. Conclusions: efficacy and considerable duration of aftereffect of single administration of Durolane SJ (small joints) as compared with placebo was demonstrated in 24 and 48 weeks. Disclosure of Interest: None declared